The influence of model parameters on model validation. Issue 12 (10th September 2019) - Infantolino, Benjamin W.; Forrester, Steph E.; Pain, Matthew T.G.; Challis, John H.
Abstract: The study examined the sensitivity of two musculoskeletal models to the parameters describing each model. Two different models were examined: a phenomenological model of human jumping with parameters based on live subject data, and the second a model of the First Dorsal Interosseous with parameters based on cadaveric measurements. Both models were sensitive to the model parameters, with the use of mean group data not producing model outputs reflective of either the performance of any group member or the mean group performance. These results highlight the value of subject specific model parameters, and the problems associated with model validation.